Dengue vaccine development by the year 2020: challenges and prospects - Wilder-Smith, Annelies (Current opinion in virology, 2020)
The first licensed dengue vaccine led to considerable controversy, and to date, no dengue vaccine is in widespread use. All three leading dengue vaccine candidates are live attenuated vaccines, with the main difference between them being the type of backbone and the extent of chimerization. While CYD-TDV (the first licensed dengue vaccine) does not include non-structural proteins of dengue, TAK-003 contains the dengue virus serotype 2 backbone, and the Butantan/Merck vaccine contains three full-genomes of the four dengue virus serotypes. While dengue-primed individuals can already benefit from vaccination against all four serotypes with the first licensed dengue vaccine CYD-TDV, the need for dengue-naive population has not yet been met. To improve tetravalent protection, sequential vaccination should be considered in addition to a heterologous prime-boost approach.
Gesehen am 18.01.2021